Venture capital and management-led, leveraged buy-outs: A European perspective - Wright, Mike; Thompson, Steve; Robbie, Ken (Journal of Business Venturing, 1992)
Management and leveraged buy-outs became phenomena of the 1980s. From beginnings in the U.S., they quickly traversed the Atlantic, spreading first to the U.K. and then throughout Europe. The venture capital industry has played a crucial role in the development of buy-outs in Europe, particularly in smaller deals in the U.K., the Netherlands, and France. This paper examines three aspects of the market for venture and development capital funded management led buy-outs in Europe. It provides a framework for analysis of the different levels of development of each country's market, it examines performance of U.K. buy-outs and addresses the extent and nature of exits. Throughout the paper use is made of the extensive database of European buy-outs developed by the authors. The main conclusions to emerge are as follows. European experience can not be compared to that in the U.S. as a single economy. There are important differences between European countries in respect of the level of buy-out activity and the extent to which conditions are or will be favourable for the development of such transactions. Conceptually, a buy-out market may be considered as requiring three main factors to be present if it is to develop: the generation of buy-out opportunities; the infrastructure to complete a transaction; and opportunities for the investors in a buy-out to realise their gains. These broad groups may be further sub-divided. The generation of opportunities will be heavily influenced by attitudes to entrepreneurial risk and hence willingness of managers to buy, the ownership structure of industry and hence the generation of entities which are for sale and the state of development of mergers and acquisition markets. The infrastructure to complete transactions includes sources of funding both in respect of venture capital availability and the ability of banks to fund transactions, the nature of legal and taxation regimes and the existence of intermediaries and advisors who can both identify and negotiate buy-outs. The existence of suitable exit routes comprises stock market flotation, sale to another group and recapitalisation possibly through a secondary buy-out. Many of these factors are similar to the conditions necessary for venture capital deals to develop. The generation of entities for sale may take various forms with succession issues in family firms, divestment of unwanted divisions, privatization of public sector activities and going privates of companies quoted on a stock market being the most important. This framework was used to analyze European buy-out markets through a combination of interview and desk research. The evidence shows that the most highly developed buy-out markets and those with the greatest short-term potential are not necessarily to be found in the largest economies. U.S. investors, who turn towards Europe to develop their markets at a time when the U.S. buy-out market is experiencing a downturn, and European investors, seeking to broaden their activities, need to be aware of these differences. As in comparable studies in the U.S., U.K. LBOs on the evidence from our survey of 182 buyouts on average produce-performance improvements. U.K. LBOs appear to undertake a greater level of new product development and asset purchase after buy-out than do their counterparts in the U.S. and have placed less emphasis on asset disposals than U.S. LBOs. Managers buying-out frequently tightened up their control of working capital. The results of our survey indicate support for both the entrepreneurial and agency cost-reduction perspectives about buy-outs, with the former perhaps being somewhat more in evidence. Exit routes are an important aspect of the buy-out market, but evidence presented here indicates that buy-outs are unlikely to exit in the way in which they originally envisaged. In particular, buy-outs that initially were aiming for flotation on a secondary tier stock market have almost invariably been sold to third parties.